2022
DOI: 10.1101/2022.06.02.22275916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long COVID is associated with extensive in-vivo neuroinflammation on [18F]DPA-714 PET

Abstract: A significant number of COVID-19 patients develop 'long COVID', a condition defined by long-lasting debilitating, often neurological, symptoms. The pathophysiology of long COVID is unknown. Here we present in-vivo evidence of widespread neuroinflammation in long COVID, using a quantitative assessment, [18F]DPA-714 PET, in two long COVID patients. We reanalyzed historical data from three matched healthy control subjects, for comparison purposes. Both patients with long COVID had widespread increases in [18F]D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
2
17
1
Order By: Relevance
“…Possible mechanisms for these neuropathologies include neuroinflammation, damage to blood vessels by coagulopathy and endothelial dysfunction, and injury to neurons 32 . Studies have found Alzheimer disease-like signalling in patients with long COVID 78 , peptides that self-assemble into amyloid clumps which are toxic to neurons 79 , widespread neuroinflammation 80 , brain and brainstem hypometabolism correlated with specific symptoms 81,82 and abnormal cerebrospinal fluid findings in non-hospitalized individuals with long COVID along with an association between younger age and a delayed onset of neurological symptoms 83 . Multilineage cellular dysregulation and myelin loss were reported in a recent preprint in patients with long COVID who had mild infections, with microglial reactivity similar to that seen in chemotherapy, known as 'chemo-brain' 42 .…”
Section: Neurological and Cognitive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible mechanisms for these neuropathologies include neuroinflammation, damage to blood vessels by coagulopathy and endothelial dysfunction, and injury to neurons 32 . Studies have found Alzheimer disease-like signalling in patients with long COVID 78 , peptides that self-assemble into amyloid clumps which are toxic to neurons 79 , widespread neuroinflammation 80 , brain and brainstem hypometabolism correlated with specific symptoms 81,82 and abnormal cerebrospinal fluid findings in non-hospitalized individuals with long COVID along with an association between younger age and a delayed onset of neurological symptoms 83 . Multilineage cellular dysregulation and myelin loss were reported in a recent preprint in patients with long COVID who had mild infections, with microglial reactivity similar to that seen in chemotherapy, known as 'chemo-brain' 42 .…”
Section: Neurological and Cognitive Systemsmentioning
confidence: 99%
“…Long COVID research has found mitochondrial dysfunction including loss of mitochondrial membrane potential 105 and possible dysfunctional mitochondrial metabolism 106 , altered fatty acid metabolism and dysfunctional mitochondriondependent lipid catabolism consistent with mitochondrial dysfunction in exercise intolerance 107 , redox imbalance 108 , and exercise intolerance and impaired oxygen extraction 100,109,110 . Studies have also found endothelial dysfunction 29 , cerebral blood flow abnormalities and metabolic changes 81,[111][112][113] (even in individuals with long COVID whose POTS symptoms abate 114 ), extensive neuroinflammation 42,80 , reactivated herpesviruses 18,21,27 , deformed red blood cells 64 Dysautonomia, particularly POTS, is commonly comorbid with ME/CFS 116 and also often has a viral onset 117 . POTS is associated with G protein-coupled adrenergic receptor and muscarinic acetylcholine receptor autoantibodies, platelet storage pool deficiency, small fibre neuropathy and other neuropathologies 118 .…”
Section: Me/cfs Dysautonomia and Related Conditionsmentioning
confidence: 99%
“…There is a strong association between occurrence of systemic inflammation and subsequent development of cognitive impairment ( Shen et al, 2019 ). Based on preclinical ( Barichello et al, 2019 ), post-mortal ( Westhoff et al, 2019 ; Schurink et al, 2020 ) and neuro-imaging ( Visser et al, 2002 ) studies, neuro-inflammation appears to play a relevant role in the development of brain dysfunction following sepsis. Therefore, inhibition of systemic inflammatory mediators might impact the development of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is a common feature in NDs involving increased production of pro-inflammatory cytokines [ 13 , 58 ]. A recent study has shown that SARS-CoV-2 mediated neuroinflammation contributes to the pathophysiology of long COVID-19 symptoms, including neurological symptoms [ 59 ]. SARS-CoV-2 is a neurotropic virus that can infect the brain, which is supported by evidence from COVID-19 patients that indicates the presence of SARS-CoV-2 viral particles in both the CNS and brain [ 6 ].…”
Section: Resultsmentioning
confidence: 99%